Penerapan Pembelajaran Saintifik Model Social Inquiry untuk Meningkatkan Hasil Belajar IPS bagi Siswa Kelas VIII B SMP - Agus Sudarmono (Jurnal Kualita Pendidikan, 2022)
This study aims to improve: (1) presentation performance to students in social studies learning, and (2) social studies learning outcomes in the material "Population Dynamics and National Development" in class VIII B odd semester students at SMP Negeri 2 Gubug, Grobogan Regency for the 2021 academic year/ 2022 through the application of the scientific learning method with the social inquiry model. This research is a classroom action research. The research was conducted in odd semester class VIII B of SMP Negeri 2 Gubug consisting of 32 students. The research was conducted in an odd semester for 3 (three) months, from July 2021 to September 2021. The research procedure in this action research basically refers to the research design used, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection on the results of the action. Based on the results of the analysis, this study concluded: (1) Through the application of the scientific learning method social inquiry model (social inquiry) can improve student presentation performance in social studies learning material "Population Dynamics and National Development" for class VIII B odd semester students of SMP Negeri 2 Gubug , Grobogan Regency for the 2021/2022 academic year. This is indicated by the increased performance of student presentations in each cycle of action taken, and (2) through the application of the scientific learning method social inquiry model can improve student learning outcomes in Social Studies learning material "Population Dynamics and National Development" for students VIII B odd semester of SMP Negeri 2 Gubug. This is indicated by the increase in the average value of learning outcomes and the number of students with learning outcomes of classification A (Very Good) and B (Good) in each cycle of action taken.